Pengaruh Submergence Ratio dan Debit Udara Terhadap Performa Airlift Pump Dua Fase Dengan Sudut Injektor 30o: Effect of Submergence Ratio and Air Flow Rate on the Performance of a Two-Phase Airlift Pump with a Injector Angle 30° - Muchammad Insan Brilian; Nurmala Dyah Fajarningrum; Nur Hayati (Universitas Pendidikan Ganesha, 2025)
The airlift pump is a device used to lift a mixture of liquid and solid particles through a vertical pipe and is capable of continuous operation. This device serves as a cost-effective solution for water lifting applications and is resistant to solid particles that may otherwise damage conventional pump components. This study aims to evaluate the performance of a two-phase airlift pump based on variations in submergence ratio and injected air flow rate. The main focus is to examine the effects of these parameters on water discharge, the resulting flow patterns, efficiency, and effectiveness of the airlift pump. Experiments were conducted using submergence ratios of h, h, and h, and air flow rates of 30 lpm, 40 lpm, 50 lpm, and 60 lpm. The test results show that increasing the submergence ratio and air flow rate leads to an increase in water discharge and efficiency up to a certain point, after which both values begin to decline. The highest efficiency and effectiveness were recorded at an air flow rate of 40 lpm with a submergence ratio of h, yielding an efficiency of 3.34% and an effectiveness of 888.60. However, once the pump reaches its peak performance, further increases in air flow rate lead to a decrease in overall performance. The observed flow patterns include bubbly, slug, and churn flow. The bubbly flow pattern typically appears at the tail end of slug flow. The results also indicate that higher submergence ratios and air flow rates produce higher water discharge, greater efficiency, and improved effectiveness of the airlift pump.